Efektivitas Intervensi Pembelajaran Berbasis Praktikum untuk Mengembangkan Literasi Memahami Gambar dan Mereduksi Stres Akademik Siswa Sekolah Indonesia Kuala Lumpur (SIKL) Malaysia - Mohammad Hefni; Fathol Haliq; Fitriyatul Qomariyah; Iswatun Hasanah; Selvi Fauziyah; Fatimatuz Zahroh (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Visual literacy and academic stress are critical issues in 21st-century education, particularly for students of Sekolah Indonesia Kuala Lumpur (SIKL) who face the dual challenges of cultural identity and academic demands. This study aimed to examine the effectiveness of science practicum-based learning in enhancing students’ ability to interpret visual representations while simultaneously reducing academic stress. The research employed a one-group pre-test and post-test experimental design involving 25 seventh-grade students, with instruments consisting of a visual literacy test and a modified Student-Life Stress Inventory (SLSI) questionnaire. The findings revealed a significant increase in students’ visual literacy scores, from an average of 50.8 to 72, with a paired t-test result of p = 0.000 (< 0.05), confirming that practicum-based learning strengthens students’ capacity to read and interpret visual representations in line with constructivist theory. Furthermore, academic stress measurement on 24 students showed that 37% were in the low-stress category, 63% in moderate stress, and none in high stress, indicating that practicum-based learning effectively alleviates academic stress. However, the relatively high proportion of moderate stress highlights the need for additional strategies such as psychosocial support and time management. This study underscores that practicum-based learning not only improves visual literacy but also serves as a humanistic approach that promotes students’ academic well-being and supports the development of 21st-century curricula.